Predictors of social intelligence, empathy, and self‐efficacy among sexual offenders. Issue 1 (7th March 2022) - Cartwright, Angie D.; Minton, Casey A. Barrio; Reyes, Ana G.; Abernathy, Meagan; Groves, Kerin K.
Abstract: The authors aimed to assess the predictive nature of social intelligence, empathy, general self‐efficacy (GSE), time in counseling, and risk‐level in a sample of sexual offenders receiving counseling services ( n = 151). No mean differences in variables were observed on the basis of victim type, offense type, or risk level. Linear regression models indicated that study variables accounted for 22% of the variance in social intelligence and 13% of the variance in empathy. In both models, GSE emerged as the strongest predictor after accounting for other variables.